The effect of density dependent emigration on spread of infectious diseases: a modelling study - Shikha Singh (Revista Latinoamericana de Hipertensión, 2019)
In this study, we proposed and analyzed an SIS mathematical model by considering population density dependent emigration. It is assumed that the disease is transmitted by direct contact of infective and susceptible populations. We also assumed that the rate of contact is emigration dependent i.e. contact rate is variable which depends on the current population of habitat as well as on non-emigrating population density of habitat. The equilibria and their stability are studied by using the stability theory of differential equations and simulation. The model analysis shows that the spread of infectious disease in habitat decreases if the rate of emigration increases but it increases as the population density of non-emigrating population increases. The simulation study of the model confirms these analytical results. Kew words: Modelling and Simulation, Mathematical model, Density dependent emigration, Stability.